PORTRAIT OF CLEAN AND HEALTHY LIVING BEHAVIOR (PHBS) OF BOARDING SCHOOL STUDENTS IN CILEGON CITY - Pertiwi, Wiwik Eko; Octofiyani, Yanti (HEARTY, 2024)
Clean and Healthy Living Behavior (PHBS) is a manifestation of healthy living orientation in individual, family and community cultures with the aim of improving, maintaining and protecting their health, both physically, mentally, and spiritually and socially. This study aims to determine the description of Clean and Healthy Living Behavior (PHBS) in Madrasah Aliyah (MA) Boarding School students in Cilegon City in 2022. This study is a descriptive study with a research population of all Madrasah Aliyah class X and XI students as many as 208 students. The sample of this study was 160 respondents taken by simple random sampling. Method using proportional sampling technique. Research shows that 51.3% of students' PHBS includes poor hands, hand washing behavior with soap and flowing water in the poor category (29.1%), healthy snack consumption behavior in the poor category (37.5%), the use of clean and healthy latrines in the poor category (44.4%), garbage disposal behavior is included in the poor category (71.9%), as many as 20.6% of students smoke at school, as many as 61.3% of students do not spit anywhere. As many as 71.9% of students litter, mosquito larvae eradication behavior is not good (58.1%). Based on the results of the study, it can be concluded that more than 50% of PHBS MA Boarding School students in Cilegon City are categorized as poor.